Magnetically treated water irrigation effect on turnip seed germination, seedling growth and enzymatic activities - Zia ul Haq; Munawar Iqbal; Yasir Jamil; Hafeez Anwar; Ayesha Younis; Muhammad Arif; M. Zeshan Fareed; Fida Hussain (Information Processing in Agriculture, 2016)
Pre-sowing magnetic field seed treatment effects on biological characteristics of vegetables and crops have been studied well. However, studies reporting irrigation with magnetically treated water are scanty. Therefore, the effect of irrigation with magnetically treated water on turnip seed germination, seedling growth and enzymatic activities was evaluated. The tap water was treated at 211 mT for 30, 45 and 60 min and used for irrigation of turnip seed and seedlings. Uniform and healthy turnip seed was sown under randomized complete block design (RCBD). The germination, emergence rate index, vigor index I and vigor index II increased up to 28.33%, 11.54%, 57.59% and 32.26%, respectively. The growth parameters such as seedling lengths, fresh & dry weights, chlorophyll content were also enhanced in response of irrigation with magnetically treated water. The seedlings irrigated with magnetically treated water showed 28.92%, 11.36% and 14.76% higher protein content, alpha amylase and protease activities, respectively vs control. Results revealed that irrigation with magnetically treated water has potential to improve turnip germination, seedling growth and enzymatic activities and this study is also extendable to other vegetables and crops for the improvement of germination and growth.